Experimental validation of a novel architecture based on a dual-stage converter for off-board fast battery chargers of electric vehicles - Monteiro, V. (2019)
The experimental validation of a novel architecture of an off-board three-phase fast battery charger for electric vehicles (EVs) with innovative operation modes is presented in this paper. The proposed EV fast battery charger is based on a dual-stage power converter (ac-dc and dc-dc) sharing the same dc-link. The ac-dc stage is used as interface between the power grid and the dc-link; it is composed by the parallel association of two full-bridge voltage-source converters, and allows to control the grid current and the dc-link voltage. The dc-dc stage is used as interface between the dc-link and the batteries; it is constituted by a bidirectional three-level asymmetrical voltage-source converter, and allows to control the current during the EV battery charging process. Compared with the traditional solutions used for EV fast battery chargers, the proposed architecture operates as interleaved converter, allowing to reduce the passive filters and the grid current harmonic distortion for the same switching frequency. Along the paper, the ac-dc and dc-dc stages, and the digital control algorithms are described in detail. The experimental validation was performed in laboratory using a developed EV fast battery charger prototype, operating through the grid-to-vehicle (G2V) and the proposed charger-to-grid (C2G) modes, exchanging active and reactive power with the power grid.